Gross Premium Income and Claims Settlement of Marine and Aviation Insurance in Nigeria. - ISIMOYA, Augustine Ogorchukwu; Akindipe, Oluwaleke Ebenezer (Acta Universitatis Danubius. Œconomica, 2022)
Maritime and aviation facilities carry a sizable percentage of world trade by volume and value, with the percentages being more significant in developing nations and creating millions of employment. The most significant point of interaction between the insured and the insurer in the maritime and aviation sectors is the claim, which is the lifeblood of the viability of insurance. This study compared claims settlement in Nigeria's marine and aviation insurance markets to gross premium income between 2011 and 2021. The Nigerian Insurers Association (NIA) annual reports and digest were used to extract information on gross premium income and gross claims paid for the time period. The data were subjected to a stationarity test, which showed that the data are stationary at the 1%, 5%, and 10% levels of significance. The computed probability value of 0.0866 using the ordinary least squares regression is larger than the 0.05 significant value, demonstrating the statistical insignificance of the data. The independent variable, gross premium income, accounts for 29.12% of the payment of the total claim, according to the linear coefficient of determination (R2= 0.291294). The link between gross premium revenue and gross claims payment for marine and aviation insurance was therefore found to be insignificant